(untitled) (France, 2012)
This Report is an independent publication commissioned by UNESCO on behalf of the international. The designations employed and the presentation of the material in this publication do not imply the expression of any opinion whatsoever on the part of UNESCO concerning the legal status of any country, territory, city or area, or of its authorities, or concerning the delimitation of its frontiers or boundaries.
Keywords: Special education,Special education,Giáo dục đặc biệt,Giáo dục đặc biệt; Methods,Study and teaching,Phương pháp,Giảng dạy và học tập